STUDY ON THE CURRENT STAGE OF DEVELOPMENT, PLANNING AND PROMOTION OF RURAL TOURISM AND AGRITOURISM IN THE ETHNOGRAPHIC AREA MARAMUREȘ - Jenica CĂLINA; Aurel CĂLINA (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The paper presents general elements regarding rural tourism, agrotourism and the tourist potential of the rural area, the unique natural and anthropic tourist heritage of the Maramureș ethnographic area. The current stage of capitalizing the tourist potential is presented, by analyzing the main forms of rural tourism practiced in the area, by determining the indicators that characterize the number of rural tourist pensions, accommodation capacity and are proposed some strategies for tourism development and tourism promotion and advertising this area, at national and international level. In the first part, a realistic and pertinent analysis was made of the specific tourist potential of the Maramureș ethnographic area, through which it is clearly different from other ethnographic areas in our country and which capitalized at its true value can be a real magnet of attraction for domestic tourists, but especially for foreign ones. The second part highlighted the evolution and development of the number of pensions and accommodation capacity in this beautiful region, in the period 2016-2020, which was significantly affected especially by the pandemic situation in our country and other neighbouring countries and the European Union. Finally, based on the real situation of the development stage and use of the tourist potential in the studied ethnographic area, a series of new strategies for the development and promotion of the rural tourism and agrotourism activity were presented.